Uczenie się demokracji od dzieciństwa – kaprys czy potrzeba współczesności? - Agnieszka Olczak (Problemy Wczesnej Edukacji)
In the modern, changing, uncertain world, life is becoming more and more complex and difficult. Only those who are well prepared for it will be able to function in this world. Thus, the article raises the question of whether teaching children democracy, liberation behaviour, participation, but also responsibility, is a fantasy, a fiction, or a whim, which teachers and researchers who seek, and parents who reject authoritarianism are often accused of, or whether it is a necessity of the modern times and an expression of an awareness that it is essential wisely to prepare the younger generation for life in contemporary society. In this paper the author also outlines the role of educational institutions that can and should be aware of this task and search for opportunities for the creation of conditions for the development of children’s democratic competences.